Evaluation of pharyngeal shape and size using anatomical optical coherence tomography in individuals with and without obstructive sleep apnoea - Walsh, J.; Leigh, M.; Paduch, A.; Maddison, K.; Philippe, D.; Armstrong, J.; Sampson, D.; Hillman, D.; Eastwood, Peter (Blackwell Publishing Ltd, 2008)
This study compared shape, size and length of the pharyngeal airway in individuals with and without obstructive sleep apnoea (OSA) using a novel endoscopic imaging technique, anatomical optical coherence tomography (aOCT). The study population comprised a preliminary study group of 20 OSA patients and a subsequent controlled study group of 10 OSA patients and 10 body mass index (BMI)-, gender- and age-matched control subjects without OSA. All subjects were scanned using aOCT while awake, supine and breathing quietly. Measurements of airway cross-sectional area (CSA) and anteroposterior (A-P) and lateral diameters were obtained from the hypo-, oro- and velopharyngeal regions. A-P : lateral diameter ratios were calculated to provide an index of regional airway shape. In all subjects, pharyngeal CSA was lowest in the velopharynx. Patients with OSA had a smaller velopharyngeal CSA than controls (maximum CSA 91 ± 40 versus 153 ± 84 mm2; P < 0.05) but comparable oro- (318 ± 80 versus 279 ± 129 mm2; P = 0.48) and hypopharyngeal CSA (250 ± 105 versus 303 ± 112 mm2; P = 0.36). In each pharyngeal region, the long axis of the airway was oriented in the lateral diameter. Airway shape was not different between the groups. Pharyngeal airway length was similar in both groups, although the OSA group had longer uvulae than the control group (16.8 ± 6.2 versus 11.2 ± 5.2 mm; P < 0.05). This study has shown that individuals with OSA have a smaller velopharyngeal CSA than BMI-, gender- and age-matched control volunteers, but comparable shape: a laterally oriented ellipse. These findings suggest that it is an abnormality in size rather than shape that is the more important anatomical predictor of OSA. © 2008 European Sleep Research Society.